On pitchforks and tomahawks - Michael Pflüger; Jens Südekum (Institute for the Study of Labor (IZA), 2007)
The core-periphery model by Krugman (1991) has two 'dramatic' implications: catastrophic agglomeration and locational hysteresis. We study this seminal model with CES instead of Cobb-Douglas upper tier preferences. This small generalization suffices to change these stark implications. For a wide range of parameters we find that the model exhibits instead a smooth and easily reversible transition from symmetry to agglomeration.
Keywords: F12; 330; Core-periphery model; new economic geography; agglomeration; bifurcation pattern; Kern-Peripherie-Beziehung; Neue ökonomische Geographie; Agglomerationseffekt; Nichtlineare dynamische Systeme; Präferenztheorie; Substitutionselastizität; Theorie